Usulan Model Tata Kelola Teknologi Informasi Pada Domain Plan And Organise Dengan Menggunakan Framework COBIT 4.1 - Amanda Paramita Salsabila; Hukama Nur Romadlon; Siti Mukaromah (Universitas Mercu Buana Yogyakarta, 2023)
Matahari Coy is a company engaged in food raw materials with a large scope that requires optimal IT involvement so that there is a need for an appropriate IT governance standard mechanism. The COBIT 4.1 framework provides a solution for implementing the IT governance model. This research focuses on the domains of the PLAN AND ORGANISE domains: PO4 (define IT processes, organizations and relationships), PO5 domain (managing IT investments), PO7 domain (IT human resource management), PO8 domain (managing quality), and the PO8 domain (managing quality). PO9 (assess and manage IT risk). This study uses management awareness methods and maturity levels in each domain respectively PO4, PO5, PO7, PO8 and PO9. Data collection is done by means of observation and interviews. Based on the calculation of the questionnaire for the PO4 process, the performance level is still lacking/low with an average value of 1.47 and it is suggested that improvements need to be made to the organization and framework of the IT process. While the PO5 process leads to level 3 (Defined Process) with an average value of 3.40 and the increase in IT budget and profit management is quite good. Furthermore, the PO7 process tends to be less/low with an average score of 2.50 and it is proposed to make improvements in terms of IT personnel selection, competency selection and personnel removal. Furthermore, the PO8 process is close to moderate with an average score of 2.17 and it is proposed to improve the practice and development of IT quality. Then PO9 tends to be less/low with an average value of 2.33 and proposed improvements to IT risk management internally and externally.